EVALUASI PENERAPAN SISTEM MANAJEMEN KESELAMATAN PERTAMBANGAN (SMKP) DAN SISTEM PENGELOLAAN PERLINDUNGAN LINGKUNGAN HIDUP PERTAMBANGAN (SPPLHP) DI PT. SUMBER ENERGI JAYA (SEJ) - Patrick Wiliam Rondonuwu; Zetly E. Tamod; Wenny ., Tilaar (AGRI-SOSIOEKONOMI, 2021)
ABSTRACTThe purpose of this research was to evaluate the implementation of the mining safety management system (SMKP) and the mining environmental protection management system (SPPLHP), analyze employee perceptions of the system, and analyze priority strategies for system improvement at PT. Sumber Energi Jaya. (SEJ). This research was conducted from October to December 2020. The research method used is a survey method with questionnaires, interviews, observations, and documentation. Determination of the sample in this study using the purposive sampling method with 50 employees as respondents. The perception data was obtained by using a questionnaire and then tested for validity and reliability with the SPSS 26 program and measured using a Likert scale. The strategy analysis used is SWOT analysis and AHP analysis with the Expert Choice program version 11. The results show that the implementation of SMKP 72% and SPPLHP 80% can be categorized as achievement at the proactive level and measurement of employee perceptions of SMKP and SPPLHP is categorized as high. The priority strategy of SMKP is to optimize company support by allocating a budget for system improvement and SPPLHP's priority strategy is to optimize the management of the mining environment by integrating information, planning, programs, budgets, procedures and structures.